Donor‐Flexible Nitrogen Ligands for Efficient Iridium‐Catalyzed Water Oxidation Catalysis. Issue 20 (5th April 2016) - Navarro, Miquel; Li, Mo; Müller‐Bunz, Helge; Bernhard, Stefan; Albrecht, Martin
Abstract: A pyridylideneamide ligand with variable donor properties owing to a pronounced zwitterionic and a neutral diene‐type resonance structure was used as a dynamic ligand at a Cp* iridium center to facilitate water oxidation catalysis, a reaction that requires the stabilization of a variety of different iridium oxidation states and that is key for developing an efficient solar fuel device. The ligand imparts high activity (nearly three‐fold increase of turnover frequency compared to benchmark systems), and exceptionally high turnover numbers, which indicate a robust catalytic cycle and little catalyst degradation. Abstract : The pyridylideneamide ligand can adapt its donor properties depending on the requirements of the metal center, a feature that is particularly useful for stabilizing different metal oxidation states on a catalytic cycle. This donor flexibility has been exploited to improve the catalytic activity of iridium water oxidation catalysts.